Cylindrically anisotropic tubular stalactite with mirror symmetry of displacement under spatially constant body force loading – a finite element model - BEDNÁRIK, Martin; KOHÚT, Igor (Contributions to Geophysics and Geodesy, 2021)
The calcite crystals of the wall of tubular stalactites (soda straws) grow, typically, with their c-axis parallel to the axis of the stalactite. With the direction of the c-axis given, the question is whether the rotation angle with respect to the c-axis is somehow determined, too. Although monocrystalline soda straws have been reported, we will here investigate the properties of hypothetical, but far more interesting, cylindrically anisotropic soda straws. It will be demonstrated that under the action of spatially constant body force, a cylindrically anisotropic axially symmetric tubular stalactite can, for some special angles of rotation, exhibit mirror symmetry of displacements, typical for isotropic or transversely isotropic tubes. For various loading modes, we will also address the question of the cylindrically anisotropic configuration optimal with regard to the strain energy.